METODE IJTIHAD IBRAHIM HOSEN - Suansar Khatib (Faculty of Sharia (Islamic Law) at Fatmawati Sukarno State Islamic University Bengkulu, 2015)
Ijtihad Method of Ibrahim Hosen, Ijtihad as the innovation of Islamic law brought theJurist in to the zenith during age of Abbasid Caliph. But the results of ijtihad often led to the pros andcons among Islamic scholars. Such as Ibrahim Hosen, his thought always contradicted to the otherislamic scholars, which caused many Islamic scholars presumed that Ibharim Hosen thought isnounsen, the Islamic scholars presumed that his thought is not through the research from the books ofmu’tabar and nor processing them correctly. Therefore, he is entitled as fake scholar, opportunistic andmatrealistic, by the other Islamic Scholars. However, Ibrahim Hosen is not the like, it is important toreview the thought of Ibrahim and his contribution in Islamic Law